Spectrum of Paediatric Breast Health Issues: Audit from a Single Center - Agnimita Giri; Trinetra Sarkar (Asian Journal of Clinical Pediatrics and Neonatology, 2023)
Paediatric breast health issues, though not a rare entity, have been overlooked. The scarcity of published literature and absence of guidelines remains a major obstacle. The aim of the study is to put forward the spectrum of the disease and to suggest a disease classification. The study involves a retrospective audit of patients presenting with paediatric breast health issues between May 2018 and March 2019.The patients were subdivided into 3 age groups (<6 years, 6-12 years and >12 years). The data was analysed. As the study involves a simple data evaluation, no comparison statistics is feasible. A total of 53 cases were analysed. Paediatric breast health issues are not infrequent. Gynaecomastia, premature thelarche and mastalgia comprises the major case loads. The study emphasizes the importance of development of guideline based paediatric breast health program in tertiary care centres.